Ekklesiologiese merkers vir missionêre gemeentebediening in ‘n postmoderne wêreld - Smit, Guillaume (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
This article explores the impact of postmodern society of the church’s understanding of herself. It lists the ecclesiological parameters within which postmodern, missional ministry should be conducted. This includes a new understanding of the biblical concept of witnessing, a new approach to the corporate gathering of the church, understanding discipleship as a life journey and not as a ministry program, developing kingdom-oriented leaders and accepting the missional challenge to tackle macro-societal challenges that impact the church, specifically through the ministry of reconciliation.